2021
DOI: 10.1111/odi.13982
|View full text |Cite
|
Sign up to set email alerts
|

Malignant peripheral nerve sheath tumour of the oral and maxillofacial region—A systematic review

Abstract: To integrate the available data published on malignant peripheral nerve sheath tumours (MPNST) of the oral and maxillofacial region. Searches in Embase, PubMed, Web of Science and Scopus were conducted for the identification of case reports/case series in English language. The risk of bias was assessed using the Joanna Briggs Institute tool. Outcomes were evaluated by Cox regression and Kaplan–Meier methods. A total of 306 articles were retrieved, 50 of which reporting 57 MPNST were included. The lesion showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 101 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…The exact etiology is not known and it may be associated with syndromes like neurofibromatosis type 1. 4 Benign Schwannoma of oral cavity is an uncommon presentation. Less then 1% arises from the oral cavity even when these areas are highly innervated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact etiology is not known and it may be associated with syndromes like neurofibromatosis type 1. 4 Benign Schwannoma of oral cavity is an uncommon presentation. Less then 1% arises from the oral cavity even when these areas are highly innervated.…”
Section: Discussionmentioning
confidence: 99%
“…They commonly presents as rapidly growing tumor with pain, tenderness, numbness, paraesthesia and burning sensation. 4 The diagnosis is based on the histopathological examination after biopsy or excision. Histologically, they are of seven subtypes: classical (verocay), plexiform, cellular, cranial nerve, melanotic, degenerated (ancient), and granular cell schwannomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,7 In our study, similar risk factors were identified. Large lesions (>10 cm), 5,17 metastasis at initial diagnosis, 15,19 and recurrence 17 were significantly poor prognostic factors of 5-year overall survival (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant schwannoma has a high risk of local recurrence and distant metastasis. Survival rate is generally low ( 8 , 15 ).…”
Section: Related Literature Learningmentioning
confidence: 99%